Leadership Talk - Aritz, Jolanta (Business Expert Press, 2014)
Ebook from IG Library ; Traditionally, management theories have taken a psychological approach to leadership, often assuming that it is a personality trait located within an individual. In contrast, the discursive approach to leadership, which is the focus of this book, assumes that leadership is created through communication practices. As a leader, this book will provide you with an in-depth look at an emerging approach to the study of business leadership that focuses on language as a vehicle for communicating leadership. The authors explore a new definition of leadership as the expression of ideas in talk or in action that are recognized by others as capable of progressing tasks or solving problems. The practical implication of this view of leadership suggests that leaders must constantly enact and communicate their relationship to their followers in such a way as to be recognized by them as a leader. Inside, you and future leaders will learn how to approach leadership more effectively as a communication practice that involves and depends upon the response of potential followers.